New Europe and the Caribbean. - SUTTON, Paul (1995)
Examines the fears of Caribbean states that the Maastricht Treaty and the single European Market (SEM) presages the end of the close relationship they shared with Europe for more than five hundred years. Assesses the likely consequences of the Single Market and the European Union in the present and future. Finds that the immediate impact of the SEM on the Caribbean is not that great but that in the mid-term, and especially in the long-term, the Caribbean has some cause for concern. The same conclusion holds for the European Union, with the added previso that the Caribbean must recognise that the spill-over from closer integration in Europe will increasingly call for nuanced policies from the Caribbean to accommodate its differential effects.